Union and Communist Party Influences on the Environment in China - Ghorbani, Majid; Gunderson, Morley; Lee, Byron (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2019)
We examine the ways in which two major and related governmental institutions of China, the Communist Party of China (CPC) and government controlled All-China Federation of Trade Unions (ACFTU), exert different effects on the attitudes and behaviour of people toward the environment. Our motivation is to see which institution is more effective in making individuals ‘aware’ of environmental issues, expressing a ‘willingness to pay’ to alleviate the problems, and ultimately to ‘act’ on the issue by altering their behaviour.Based on theories of planned behaviour and social learning, we hypothesize that membership in the CPC as well as in the ACFTU fosters an ‘awareness’ of environmental problems and a ‘willingness to make a sacrifice’ to protect the environment, but that members of the ACFTU are more likely than members of the CPC to act on the issue by altering their behaviour.We test our hypothesis based on a nationally representative sample (n = 3112) from the 2010 Chinese General Social Survey (CGSS). Our results indicate that both the Party and the union have positive effects on ‘awareness’ and ‘willingness to pay’, but the union effect is generally stronger and only it (and not the Party) affects individual behaviour toward protecting the environment.Unions in China are generally regarded as having little or no independent power to organize workers and engage in free collective bargaining. Their role is to foster harmony between workers and employers and to co-opt grassroots actions, wildcat strikes and the growth of independent unions, all in the interest of fostering stability and growth. While this is undoubtedly the case, our results are consistent with an emerging view of a more variegated picture of Chinese trade unions that highlights some more positive elements, in our case, fostering ‘actions’ to improve the environment in China.